5-Year survival after splenectomy in a patient with recurrent cutaneous melanoma: a case report. Issue 6 (2nd November 2018) - De Roeck, Lynn; Wuyts, Laura; Peters, Benjamin; Ruppert, Martin
Abstract: Objective: Splenic metastases of melanoma are uncommon and generally part of a disseminated disease with a poor prognosis. In case of solitary visceral metastasis, surgical resection often remains an effective treatment. This case describes a long-term survival after splenectomy for a recurrent melanoma. Methods: We present a 55-year-old female with a solitary splenic metastasis. Her medical history revealed a melanoma of the foot in 2007 and an in-transit metastasis in 2011. A PET-CT revealed in 2012 the presence of a small aspecific lesion in the spleen. Close follow-up was chosen. Since PET-CT and MRI showed a progressive lesion, a laparoscopic splenectomy was performed. Results: Histological report confirmed the diagnosis of a metastatic lesion. Sixty months after the first radiographic evidence of the splenic metastasis, follow-up revealed no signs of residual disease. Conclusions: Although current systemic approaches demonstrate to provide clinically important benefit, patients with oligometastatic disease should be evaluated for surgical metastasectomy. A laparoscopic approach for splenic metastasis is shown to be a safe treatment. This disease-free survival of 60 months in a patient with a history of an in-transit metastasis has not been published before. A splenectomy for a solitary metastasis could prolong the survival, even in a recurrent melanoma.